Sistem Pencarian dan Rekomendasi Tukang Bangunan Menggunakan Mobile-Based dan GPS - Marchel Thimoty Tombeng; Semmy Taju; Ferrell Sanger; Reynaldo Daingah (Fakultas Ilmu Komputer, Universitas Klabat, 2023)
In the current digital era, information technology-based applications are rapidly evolving and becoming increasingly essential in everyday life. One type of application that is gaining popularity among the public is recommendation applications, especially those for finding handyworkers. Airmadidi is one of the cities in Indonesia with many boarding houses offering various facilities and prices. However, for newcomers seeking handyworkers in the city, finding the right one for their needs can be a challenging and exhausting task. Therefore, there is a need for a recommendation and handyworker search application system that can assist seekers in addressing issues in their boarding houses or homes according to their specific requirements. This application system will gather information about available handyworkers in Airmadidi and provide recommendations based on users' preferences and needs.The aim of this research is to design a recommendation and handyworker search application in Airmadidi using an appropriate software development method supported by the latest technology. This application system is expected to help users easily and efficiently find handyworkers that match their needs. The research methodology employed in this writing includes interviews, literature reviews, and system design using the SDLC (Software Development Life Cycle) method with a spiral model. The stages of the spiral model With the existence of this recommendation and handyworker search application system, searching for handyworkers in Airmadidi is expected to become easier, more efficient, and effective for seekers. Additionally, this research can serve as a reference for similar studies in other areas.